A review on the recent advancements on nanoparticles drug delivery approaches in anti-cancer treatment - Hoque, Syeda Mehren (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.